Sistem Pakar Diagnosa Tingkat Depresi Mahasiswa Tugas Akhir dengan Algoritma Teorema Bayes - Krisantus Jumarto Tey Seran; Hevi Herlina Ullu (STMIK Banjarbaru, 2025)
Students at Timor University consistently face the challenge of Final Projects. This presents a unique hurdle, and a significant number of students experience depression during this phase. Consequently, this impacts the smooth progression of guidance and the graduation rate for each semester. Therefore, early detection and prevention measures are crucial for students in the final project phase. This effort involves developing a web-based expert system to facilitate the identification of depression levels in students by their supervisors. The expert system utilizes Bayes' Theorem to provide an accuracy rating for the level of depression experienced by a student based on observable symptoms. The system development employs the Rapid Application Development (RAD) methodology. The research data comprises 28 symptom data points and three levels of depression (Mild, Moderate, Severe). System testing results demonstrate its effectiveness in measuring the depression levels of students at Timor University with an accuracy rate of 84%.Keywords: Student; Depression; Expert System; Theorem Bayes AbstrakMahasiswa Universitas Timor selalu dihadapkan dengan persoalan Tugas Akhir. Hal ini tentunya menjadi tantangan sehingga mengakibatkan mahasiswa mengalami depresi pada saat melaksanakan tugas akhir. Akibatnya, berpengaruh dalam kelancaran proses bimbingan serta persentase kelulusan untuk setiap periode wisuda kampus. Untuk itu perlu dilakukan pencegahan (deteksi) dini bagi mahasiswa yang sedang dalam periode tugas akhir. Upaya yang dilakukan adalah dengan membangun sistem pakar berbasis website yang mempermudah dosen pembimbing dalam mendeteksi tingkat depresi yang dialami seorang mahasiswa. Sistem pakar yang dibangun menggunakan Teorema Bayes untuk memberikan nilai akurasi pada tingkatan mana seorang mahasiswa berada berdasarkan gejala yang terlihat dan Metode RAD dalam pengembangan sistem. Data penelitian yang digunakan adalah 28 data gejala dan tiga tingkatan depresi (Ringan, Sedang, Tinggi). Hasil pengujian sistem membuktikan bahwa sistem ini dapat digunakan untuk mengukur tingkat depresi mahasiswa di Universitas Timor dengan tingkat persentase 84%. Kata kunci: Mahasiswa; Depresi; Sistem Pakar; Teorema Bayes